THE INFLUENCE OF SERVICE QUALITY, RELIGIOUS COMMITMENT AND TRUST ON THE CUSTOMERSâ SATISFACTION AND LOYALTY AND DECISION TO DO THE TRANSACTION IN MANDIRI SHARIA BANK OF JAWATIMUR - Hidayat, Rachmad; Akhmad, Sabarudin (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2015)
This study tested the causal relationship of service quality, religious commitment and trust on customersâ satisfaction, loyalty and decision to repeat their transaction in sharia banking services. This research used quantitative approach to describe the causal relationship between the variables through hypothesis testing. The samples in this research are 160 respondents.Â Structural equation modeling (SEM) is used to analyze this research. This research findings shows that the quality of service and customersâ trust, satisfaction and loyalty simultaneously influenced the decision to repeat their transaction in that banking service. The customersâ satisfaction and loyalty are intervening variables that linked the service quality and the customersâ trust with the decision to repeat their banking transaction. The religious commitment had insignificant influence toward the service quality; however, it had significant influence toward the loyalty and decision to repeat their banking transaction.Â —–Penelitian ini menguji hubungan kausalitas kualitas layanan, kepercayaan dan komitmen beragama nasabah terhadap kepuasan, loyalitas dan keputusan bertransaksi ulangÂ layanan perbankan syariah. Penelitian ini menggunakan pendekatan kuantitatif yang bermaksud memberikan penjelasan hubungan kausalitas antar variabel melalui pengujian hipotesis. Jumlah sampel penelitian sejumlah 160 responden. Analisis yang digunakan adalah model persamaan struktural (Structural Equation Modeling atau SEM). Hasil penelitian menunjukkan bahwa kualitas layanan dan kepercayaan nasabah, kepuasan dan loyalitas secara bersama-sama berpengaruh terhadap keputusan bertransaksi ulangÂ layanan perbankan. Kepuasan dan loyalitas nasabah menjadi variabel intervening yang menghubungkan kualitas layanan dan kepercayaan nasabah dengan keputusan bertransaksi ulangÂ layanan perbankan. Komitmen beragama berpengaruh tidak signifikan terhadap kualitas layanan, namun berpengaruh signfikan terhadap loyalitas dan keputusan bertransaksi ulangÂ layanan perbankan